13. CLINICAL AND PARACLINICAL CHARACTERISTICS OF SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS TREATED AT THE NATIONAL DERMATOLOGY HOSPITAL FROM 01/2022 TO 8/2023 (Vietnam Journal of Community Medicine, 2024)
Objective: To describe the clinical and paraclinical characteristics of female systemic lupus erythematosus patients.Subjects and methods: Study on a series of cases of 65 female systemic lupus erythematosus patients who came for examination and treatment at the National Dermatology Hospital from January 2022 to August 2023.Results: The average age of disease was 30.72±15.1. The age group 10-19 accounts for the highest proportion (33.8%), and the age group 0-9 accounts for the lowest proportion (3.1%). The average duration of illness of the patients was 10.15±4.4 months. Skin lesions in SLE patients are diverse, including specific and nonspecific skin lesions. Acute skin lesions are the most common, accounting for 60%, followed by subacute 27.7% and chronic 12.3%. Butterfly rash lesions are most common in specific skin lesions (36.9%), and photosensitivity lesions are the most common in non-specific skin lesions (52.3%). The positive rate of Anti Smith autoantibodies is 23.1%; anti Ro/SSA was 46.2% and anti LA/SSB was 10.8%.Conclusion: Skin lesions are very common and diverse in patients with systemic lupus erythematosus. Patients need to be examined carefully to detect early and fully all types of specific and non-specific lupus skin lesions, contributing to early diagnosis of SLE disease.
Keywords: National hospital of dermatology & venereology, systemic lupus erythematosus, clinical, subclinical